Stress-induced obesity in mice causes cognitive decline associated with inhibition of hippocampal neurogenesis and dysfunctional gut microbiota - Liu, Yu-e; Zhao, Zhihuang; He, Haili; Li, Liangyuan; Xiao, Chenghong; Zhou, Tao; You, Zili; Zhang, Jinqiang (Frontiers in Microbiology, 2024)
Effects of stress on obesity have been thoroughly studied in high-fat diet fed mice, but not in normal diet fed mice, which is important to clarify because even on a normal diet, some individuals will become obese under stress conditions. Here we compared mice that showed substantial weight gain or loss under chronic mild stress while on a normal diet; we compared the two groups in terms of cognitive function, hypothalamic–pituitary–adrenal signaling, neurogenesis and activation of microglia in hippocampus, gene expression and composition of the gut microbiome. Chronic mild stress induced diet-independent obesity in approximately 20% of animals, and it involved inflammatory responses in peripheral and central nervous system as well as hyperactivation of the hypothalamic–pituitary–adrenal signaling and of microglia in the hippocampus, which were associated with cognitive deficits and impaired hippocampal neurogenesis. It significantly increased in relative abundance at the phylum level (Firmicutes), at the family level (Prevotellaceae ucg − 001 and Lachnospiraceae NK4a136), at the genus level (Dubosiella and Turicibacter) for some enteric flora, while reducing the relative abundance at the family level (Lactobacillaceae and Erysipelotrichaceae), at the genus level (Bacteroidota, Alistipes, Alloprevotella, Bifidobacterium and Desulfovibrio) for some enteric flora. These results suggest that stress, independently of diet, can induce obesity and cognitive decline that involve dysfunctional gut microbiota. These insights imply that mitigation of hypothalamic–pituitary–adrenal signaling and microglial activation as well as remodeling of gut microbiota may reverse stress-induced obesity and associated cognitive decline.